Public Sentiment among Peasantry of “Revolutionary Turning Point” Generation at turn of 1920—1930s - A. A. Slezin; K. A. Yakimov (Научный диалог, 2022)
The paper studies characteristics of the public sentiment among peasantry of the “revolutionary turning point” generation (born at the turn of XIX—XX centuries). The relevance of the chosen topic lies in the need to carry out a comprehensive study of the state of public opinion of the villagers at the turn of the 1920—1930s through the prism of the “generational” section. Based on a wide range of archival documents and periodicals, most of which are introduced into scientific circulation for the first time, the paper focuses on the analysis of the main ways of adapting peasant mentality in the context of agricultural collectivization. Particular attention is paid to the analysis of the sources and forms of manifestation of the protest moods among peasants. The conducted research showed the ambiguous attitude of peasantry towards collectivization. The authors come to the conclusion that in most cases the transition to collective farms caused discontent among villagers, and the collective farm system itself was associated with hunger and ruin. It is shown that a significant part of peasantry of the “revolutionary turning point” generation perceived the state policy in the countryside as a return to the prerevolutionary order. It is noted that the excesses during dispossession contributed to the intensification of the confrontation between the various property strata of peasantry.